High-throughput DNA methylation analysis in anorexia nervosa confirms TNXB hypermethylation. (3rd April 2018) - Kesselmeier, Miriam; Pütter, Carolin; Volckmar, Anna-Lena; Baurecht, Hansjörg; Grallert, Harald; Illig, Thomas; Ismail, Khadeeja; Ollikainen, Miina; Silén, Yasmina; Keski-Rahkonen, Anna; Bulik, Cynthia M.; Collier, David A.; et al.
Abstract: Objectives: Patients with anorexia nervosa (AN) are ideally suited to identify differentially methylated genes in response to starvation. Methods: We examined high-throughput DNA methylation derived from whole blood of 47 females with AN, 47 lean females without AN and 100 population-based females to compare AN with both controls. To account for different cell type compositions, we applied two reference-free methods (FastLMM-EWASher, RefFreeEWAS) and searched for consensus CpG sites identified by both methods. We used a validation sample of five monozygotic AN-discordant twin pairs. Results: Fifty-one consensus sites were identified in AN vs. lean and 81 in AN vs. population-based comparisons. These sites have not been reported in AN methylation analyses, but for the latter comparison 54/81 sites showed directionally consistent differential methylation effects in the AN-discordant twins. For a single nucleotide polymorphism rs923768 in CSGALNACT1 a nearby site was nominally associated with AN. At the gene level, we confirmed hypermethylated sites at TNXB . We found support for a locus at NR1H3 in the AN vs. lean control comparison, but the methylation direction was opposite to the one previously reported. Conclusions: We confirm genes like TNXB previously described to comprise differentially methylated sites, and highlight further sites that might be specifically involved in AN starvation processes.